Etický komplex, morálne emócie a normy v partnerstve - Táňa Grauzlerová (AntropoWebzin, 2011)
This project is focused on exploring the relationship between the set of dominant ethical norms in a given society and moral emotions which emerge as an effect of breaking these norms. The domain which I focus on are norms from the area of partnership. In this paper, I use the theory of ethical complex of anthropologist Richard Shweder and the theoretical model of social intuition of psychologist Jonathan Haidt. The main purpose of the fieldwork is the examination of the social intution model, which stresses the role of social persuasion in making moral judgements. In this connection, I want to explore which ethical complex is prevalent in a given society, and which partnership norms are referred to. I try to show the „behaviour“ of the model in empirical examples, and explore particular factors that affect it. Research methods are participant observation, informal interviews, semi- and formal interviews (in the form of model situations), and also notation of nonverbal emotional communication. In this paper, I focus on presenting empirical data relating to ethical complex.